Lingkungan Digital: Analisis Kesalahan Berbahasa Indonesia pada Platform Tiktok - Yerni Meikristian Gulo; Sitti Ainie; Zahra Nasriani Nst; Mutiara Dinda Azizah; Wisman Hadi; Mustika Wati Siregar (Universitas Palan, 2024)
Language is the identity of a country or region because language is the most important element of communication or the most important means of communication. This study uses a qualitative approach with a descriptive research format. The results of the data obtained were analyzed in depth, then compared to obtain more relevant research results. The results of the study showed a number of important findings regarding language errors in the use of TikTok social media. These findings not only reflect the types of errors that often occur, but also reveal the factors that influence them and their impact on their language development. Lack of understanding in communication can lead to misunderstandings and conflicts, and reduce the quality of social interaction.